Impact of BMI and waist circumference on epigenome-wide DNA methylation and identification of epigenetic biomarkers in blood: an EWAS in multi-ethnic Asian individuals - Chen, Yuqing (BioMed Central Ltd, 2022)
10.1186/s13148-021-01162-x